Strategi Pendidikan Islam Berbasis Moderasi Beragama Melalui Ekspresi Karnaval Budaya Pada Acara Haflah Khatmil Qur’an Pesantren Al-Asya’ariyyah Wonosobo - Robingun Suyud El Syam (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2023)
Khatmil Qur'an is a culture in various Islamic boarding schools that study the Qur'an, but the agenda of each pesantren is different in line with the tradition of the pesantren. Interestingly at the Al-Asy'ariyyah Islamic boarding school, there is a cultural carnival that presents various cultural attributes from various regions in Indonesia. So this article aims to find answers to the big question, "how is Islamic education based on religious moderation through expressions of cultural carnivals on the haflah khatmil Qur'an agenda at the Al-Asya'ariyyah Islamic Boarding School, Wonosobo". Through field research it was found that the cultural carnival at the al-Asy'ariyyah Islamic boarding school was used as a strategy for the pesantren to provide education to the community, that cultural essences needed to be preserved because they conflicted with religion. The fact that the Koran actually instructed the Prophet Muhammad to teach Islam in a gentle and tolerant way. Thus, the expression of cultural carnivals in Islamic boarding schools is the maturity of the scholars in presenting the Qur'an and hadith as part of the embodiment of religious moderation-based education.